The Fact of Ta‘rîb in Arab Lenguage - Aktaş, Sahip; Kırkız, Mustafa (Fırat University, 2016)
Throughout the history, there has been an ongoing change and advance in Arabic vocabulary. One of the ways of these changes in Arabic is Ta'rib. The essence of the Ta'rib as a fact dates back to the Ignorance Era. Scholarly studies about Ta'rib have begun to emerge in the early first century of Hegira and continued almost without interruption, and left a rich literature behind. However, a consensus about the concept of Ta'rib could not have been put forward despite the rich literature. The definitions which are done with reflex of protecting the language or considering the thresholds seen important in terms of impact on Arab language draw attention as one of the most important obstacles in front of the formation of a consensus

Tarihin akışı içerisinde Arapçanın söz dağarcığında sürekli gelişme ve değişme meydana gelmiştir. Arapçada meydana gelen bu gelişme ve değişme yollarından biri de ta‘rîbdir. Bir olgu olarak ta‘rîbin varlığı, Cahiliye dönemine kadar uzanmaktadır. Ta‘rîbe dair ilmi çalışmalar, hicrî birinci asrın erken dönemlerinden itibaren ortaya çıkmaya başlamış, neredeyse kesintisiz bir şekilde devam etmiş ve geriye zengin bir literatür bırakmıştır. Ancak bu zengin literatüre rağmen ta‘rîb kavramının uzlaşı sağlanan bir tanımı ortaya konulamamıştır. Dili koruma refleksleriyle veya Arap dili üzerinde etkisi bakımından önemli görülen eşikler göz önünde bulundurularak yapılan tanımlar, tanım etrafında bir konsensüsün oluşmasının önündeki en önemli engellerden biri olarak dikkat çekmektedir
ARAP DİLİNDE TA‘RÎB OLGUSU